On certain Peruvian type localities of birds (Aves) in Mlíkovský (2009) - Hurtado, Natali; Gamarra-Toledo, Víctor (Zootaxa, 2019)
According to the ICZN (1999), the type locality is where the specimen used as holotype, syntype or lectotype was collected (Art. 76). As such, the type locality is a source of information about the habitat and geographical occurrence of a taxon. Topotypes, specimens collected within the type locality of a species or subspecies, have been used in comparison with other specimens to corroborate the identity of the latter (e.g. Tautz et al. 2003; Vuataz et al. 2011). Other studies have used type localities in reporting apparent extinctions (e.g. Williams 2015), or degradation of the taxon’s habitat (e.g. Wirth 2018). Thus, type localities have information value for scientific collections, and may be of special conservation concern.